1986
DOI: 10.1079/bjn19860065
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microflora, morphology and enzyme activity in zinc-deficient and Zn-supplemented rats

Abstract: 1. Immature, male Wistar rats were given a low-zinc diet (2 mg/kg) for 22-24 d. Control groups received a similar diet supplemented with 58 mg Zn/kg either ad lib., or in amounts matched to the consumption of the Zn-deficient group. Food consumption, rate of growth and food conversion efficiency were markedly lower in the Zn-deficient group of rats compared with controls. Appetite, growth rate and food utilization improved dramatically over a subsequent 4 d period of Zn supplementation. 2.Morphological examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 19 publications
3
26
0
Order By: Relevance
“…The present study did not assess coliform population diversity, but CFU counts suggest that ZnO had no effect on the total number of E. coli per gram of ileal digesta or feces. This is in agreement with previous studies (Southon et al 1986;Jensen-Waern et al 1998). Southon et al (1986) reported that severe dietary Zn depletion did not reduce the number of viable bacteria present in either the small or large intestine.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The present study did not assess coliform population diversity, but CFU counts suggest that ZnO had no effect on the total number of E. coli per gram of ileal digesta or feces. This is in agreement with previous studies (Southon et al 1986;Jensen-Waern et al 1998). Southon et al (1986) reported that severe dietary Zn depletion did not reduce the number of viable bacteria present in either the small or large intestine.…”
Section: Discussionsupporting
confidence: 83%
“…This is in agreement with previous studies (Southon et al 1986;Jensen-Waern et al 1998). Southon et al (1986) reported that severe dietary Zn depletion did not reduce the number of viable bacteria present in either the small or large intestine. Hence, the mechanism by which supplemented ZnO prevents post-weaning diarrhea remains unclear.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The rates of enterocyte proliferation and migration are affected by a variety of factors. An overt nutrient deficiency, most notably for zinc [80], vitamin A [85], and cyanocobalamin (B12) [95], will affect intestinal physiology. Glutathione is a crucial antioxidant in the gastrointestinal mucosa that is also formed from glutamine [55,72].…”
Section: Early Malnutrition On Development Of the Gastrointestinal Tractmentioning
confidence: 99%